Revisiting 'lazy native' myth - Abd Razak, Dzulkifli (2007)
IN the issue of Forbes (July 2), there was a ranking of 100 celebrities based on popularity and earnings. As expected, it was dominated by showbiz artistes and authors. None were from the academe. If a similar list was attempted in Malaysia, the ranking may be quite identical, with nobody from the academe. This is nothing to gripe about, knowing that people in showbiz are anytime more popular and richer. That is just how things are. More often, intellectual personalities are in the "backroom", preoccupied with their thoughts and ideas. The image of the absentminded professor is all pervasive — they are hardly celebrity material. But some of them are towering personalities, to whom the public owe so much, unknowingly, most of the time. In their own quiet way, their ideas influence and shape the thinking of society. We only begin to realise their greatness once they are gone.